Targeting Energy Metabolic and Oncogenic Signaling Pathways in Triple-negative Breast Cancer by a Novel Adenosine Monophosphate-activated Protein Kinase (AMPK) Activator - Lee, Kuen-Haur (American Society for Biochemistry and Molecular Biology, 2011)
The antitumor activities of the novel adenosine monophosphate-activated protein kinase (AMPK) activator, OSU-53, were assessed in in vitro and in vivo models of triple-negative breast cancer. OSU-53 directly stimulated recombinant AMPK kinase activity (EC(50), 0.3 μm) and inhibited the viability and clonogenic growth of MDA-MB-231 and MDA-MB-468 cells with equal potency (IC(50), 5 and 2 μm, respectively) despite lack of LKB1 expression in MDA-MB-231 cells. Nonmalignant MCF-10A cells, however, were unaffected. Beyond AMPK-mediated effects on mammalian target of rapamycin signaling and lipogenesis, OSU-53 also targeted multiple AMPK downstream pathways. Among these, the protein phosphatase 2A-dependent dephosphorylation of Akt is noteworthy because it circumvents the feedback activation of Akt that results from mammalian target of rapamycin inhibition. OSU-53 also modulated energy homeostasis by suppressing fatty acid biosynthesis and shifting the metabolism to oxidation by up-regulating the expression of key regulators of mitochondrial biogenesis, such as a peroxisome proliferator-activated receptor γ coactivator 1α and the transcription factor nuclear respiratory factor 1. Moreover, OSU-53 suppressed LPS-induced IL-6 production, thereby blocking subsequent Stat3 activation, and inhibited hypoxia-induced epithelial-mesenchymal transition in association with the silencing of hypoxia-inducible factor 1a and the E-cadherin repressor Snail. In MDA-MB-231 tumor-bearing mice, daily oral administration of OSU-53 (50 and 100 mg/kg) suppressed tumor growth by 47–49% and modulated relevant intratumoral biomarkers of drug activity. However, OSU-53 also induced protective autophagy that attenuated its antiproliferative potency. Accordingly, cotreatment with the autophagy inhibitor chloroquine increased the in vivo tumor-suppressive activity of OSU-53. OSU-53 is a potent, orally bioavailable AMPK activator that acts through a broad spectrum of antitumor activities.